Safety of Mesenchymal Stem Cells for Clinical Application - Youwei Wang; Zhi-bo Han; Yong-ping Song; Zhong Chao Han (Hindawi Limited, 2012)
Mesenchymal stem cells (MSCs) hold great promise as therapeutic agents in regenerative medicine and autoimmune diseases, based on their differentiation abilities and immunosuppressive properties. However, the therapeutic applications raise a series of questions about the safety of culture-expanded MSCs for human use. This paper summarized recent findings about safety issues of MSCs, in particular their genetic stability in long-term in vitro expansion, their cryopreservation, banking, and the role of serum in the preparation of MSCs.